Chemo-Enzymatic Baeyer–Villiger Oxidation Facilitated with Lipases Immobilized in the Supported Ionic Liquid Phase - Anna Szelwicka; Anna Wolny; Miroslawa Grymel; Sebastian Jurczyk; Slawomir Boncel; Anna Chrobok (Materials, 2021)
A novel method for chemo-enzymatic Baeyer–Villiger oxidation of cyclic ketones in the presence of supported ionic liquid-like phase biocatalyst was designed. In this work, multi-walled carbon nanotubes were applied as a support for ionic liquids which were anchored to nanotubes covalently by amide or imine bonds. Next, lipases B from Candida antarctica, Candida rugosa, or Aspergillus oryzae were immobilized on the prepared materials. The biocatalysts were characterized using various techniques, like thermogravimetry, IR spectroscopy, XPS, elemental analysis, and SEM-EDS microscopy. In the proposed approach, a biocatalyst consisting of a lipase as an active phase allowed the generation of peracid in situ from the corresponding precursor and a green oxidant–hydrogen peroxide. The activity and stability of the obtained biocatalysts in the model oxidation of 2-adamantanone were demonstrated. High conversion of substrate (92%) was achieved under favorable conditions (toluene: n-octanoic acid ratio 1:1 = v:v, 35% aq. H2O2 2 eq., 0.080 g of biocatalyst per 1 mmol of ketone at 20 °C, reaction time 4 h) with four reaction cycles without a drop in its activity. Our ‘properties-by-design’ approach is distinguished by its short reaction time at low temperature and higher thermal stability in comparison with other biocatalysts presented in the literature reports.